Biodiesel : máquina natural de desarrollo en Nicoya, Guanacaste = Biodiesel : Nicoya, Guanacaste natural development machine - Bermúdez Carrillo, Luis Alberto 1977-
This paper aims at inquiring whether the Nicoya County has the legal, financial, climatic, and marketing conditions for castor-seed biodiesel production. The research hypothesis states whether or not there are conditions to produce castor seed derivatives as a form of clean energy in the Nicoya County. The study is grounded on an exploratory research design and involved data collection procedures such as castor-seed market information, history, uses and development in Costa Rica. Secondary sources included internet websites, books, magazines, newspapers and data gathered from businesses. Conclusions made it possible to determine that there is no legal hindrance for the seed planting and commercializing as there is actually openness to clean energies. In fact, there are various financial products as well as institutions that support the development of renewable energy products. In terms of competitive analysis, it was found that the market is fully open as seen from any of Michael Porter´s five market participants.